2017
DOI: 10.14474/ptrs.2017.6.3.127
|View full text |Cite
|
Sign up to set email alerts
|

Effect of repetitive wrist extension with electromyography-triggered stimulation after stroke: a preliminary randomized controlled study

Abstract: Objective: The purpose of this study was to explore the effect of repetitive wrist extension task training with electromyography (EMG)-triggered neuromuscular electrical stimulation (NMES) for wrist extensor muscle recovery in patients with stroke. Design: Randomized controlled trial. Methods: Fifteen subjects who had suffered a stroke were randomly assigned to an EMG-triggered NMES group (n=8) or control group (n=7); subjects in both groups received conventional therapy as usual. Subjects in the experimental … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(12 citation statements)
references
References 41 publications
0
12
0
Order By: Relevance
“…Four studies [16][17][18]30 were excluded because of missing information (mean and/or SD) needed for data pooling. The following outcome measures were identified from the studies and pooled: (1) FMA-UE, 24,25,29,31,33,[35][36][37][38]40,41 (2) reaction time, 19,20,28,39 (3) force, 26,32,39 and (4) range of movement (ROM). 22,26 Since 6 studies compared more than 2 groups, additional grouping was done.…”
Section: Effects Of Emg-nmes On Measures In the Icf Body Structure Anmentioning
confidence: 99%
See 3 more Smart Citations
“…Four studies [16][17][18]30 were excluded because of missing information (mean and/or SD) needed for data pooling. The following outcome measures were identified from the studies and pooled: (1) FMA-UE, 24,25,29,31,33,[35][36][37][38]40,41 (2) reaction time, 19,20,28,39 (3) force, 26,32,39 and (4) range of movement (ROM). 22,26 Since 6 studies compared more than 2 groups, additional grouping was done.…”
Section: Effects Of Emg-nmes On Measures In the Icf Body Structure Anmentioning
confidence: 99%
“…Studies were published between 1998 16 and 2017. [38][39][40][41] Figure 1 shows the selection of studies included in the systematic review and the main reasons for exclusion.…”
Section: Study Identification and Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations
“…This phenomenon could not be noticed in patients who use only NMES, although they also improved in functional tests. In [9], [12], and [13], there are pieces of evidence for the positive effects of NMES initiated by sEMG in various configurations. However, [14] presented a systematic review and meta-analysis of this modality's benefits and concluded that these are larger and evident in chronic cases.…”
mentioning
confidence: 99%